2022
DOI: 10.4315/jfp-21-397
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of the Impact of a Food Safety Intervention on Consumer Poultry Washing

Abstract: This study tested the effectiveness of an educational intervention on consumer poultry washing using video observation of meal preparation with participants who self-reported washing poultry. Treatment group participants received three emails containing messages the U.S. Department of Agriculture has used on social media (video and infographics) related to poultry preparation, including advising against washing it. Participants were observed cooking chicken thighs (inoculated with traceable nonpathogenic Esche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Contamination frequency was ,20% for most surfaces (Fig. 1A), comparable with findings of previous studies (4,12,29,33), but lower than that of other studies (10). Most research on the cross-contamination of kitchen surfaces due a Significance set at P , 0.0500. b Any observations for which multiple cutting boards or knives were used or video was not retrievable were not included in the analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Contamination frequency was ,20% for most surfaces (Fig. 1A), comparable with findings of previous studies (4,12,29,33), but lower than that of other studies (10). Most research on the cross-contamination of kitchen surfaces due a Significance set at P , 0.0500. b Any observations for which multiple cutting boards or knives were used or video was not retrievable were not included in the analysis.…”
Section: Discussionsupporting
confidence: 88%
“…2A). To our knowledge, spice containers as a common recipient surface for microbial cross-contamination has been seldom reported, although up to 70% of spice containers were cross-contaminated in a couple of studies documenting this surface type (10,34), with a 5 to 6% contamination rate found in a similar study by our group involving whole pieces of raw chicken (33). In addition, the mean concentration of MS2 on spice containers, 6.2 log GEC (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…This finding aligns with previous studies where recipe blogs and videos were reported to have a lack of food safety messages such as handwashing and cleaning and sanitation (Barrett and Feng, 2021; Morrison and Young, 2019). Moreover, Shumaker et al. (2022) conducted an observation study of consumers' meal preparation and they found that very few consumers performed proper handwashing and cleaning and sanitation practices.…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated hands are one of the principal vehicles for cross-contamination in the kitchen (Evans and Redmond, 2018;Shumaker et al, 2022). The effectiveness of handwashing YouTube videos of dried wood ear mushrooms in reducing the risk of cross-contamination has been widely studied.…”
Section: Food Safety Implications Of Rehydrationmentioning
confidence: 99%
“…in chicken meat was reported in India (58%) [ 15 ], Japan (60%) [ 16 ], Korea (45.8%) [ 17 ], and Malaysia (39.2%) [ 18 ]. The possible reason for this low prevalence might be the ready-to-cook chicken meat in supermarkets, and multiple washing steps reduce the contamination possibilities of these meats [ 19 ].…”
Section: Discussionmentioning
confidence: 99%